Lire la tradition orale, écrire l’histoire crie - Morantz, Toby (Anthropologie et Sociétés, 2002)
This paper follows from an earlier one in which the author questioned whether non-Native historians have the linguistic and analytic tools to interpret oral traditions and oral histories in ways that retained their integrity and cultural meaning; it concluded we do not. Here, the focus is on salvaging what is possible from these oral accounts as a way of drawing Native understanding and insights into the writing of our western-dominated histories. Under the auspices of museum programs, anthropologists have been in the field in eastern James Bay since the late 1960s and have deposited extensive reports, consisting not only of interviews but translations of oral traditions and history of an era before the Crees were more closely drawn into the industrial society. This paper analyzes these collections to furnish examples of the subjects covered and ways in which the orientation of the subjects has been determined by the interviewer. Although the author continues to maintain that such reproduction of the oral accounts wrenches them from their cultural context, she argues that what can be extrapolated from them provides vital insights into the activities and outlook of the Crees of a bygone era and are essential to writing twentieth century history. Dans un précédent article, auquel celui-ci fait suite, l’auteure avait posé la question suivante : les historiens non autochtones possèdent-ils les outils linguistiques et analytiques propres à interpréter les récits relevant de la tradition et de l’histoire orales, de manière à en conserver l’intégrité et la signification culturelle? L’article concluait que non. Ici, l’attention se porte sur ce qu’il est possible de sauvegarder de ces récits oraux pour introduire dans notre rédaction euro-dominée de l’histoire les conceptions et la compréhension qu’en ont les Autochtones. À partir de la fin des années soixante, sous les auspices de programmes muséaux, des anthropologues se sont rendus sur le terrain à l’est de la baie James et ont produit d’imposants rapports, qui ne ...